Challenging Global Group Audits: The Perspective of US Group Audit Leads* - Downey, Denise Hanes; Westermann, Kimberly D. (Contemporary Accounting Research, 2021)
ABSTRACT Regulators are concerned about the quality of group audits because of poor inspection results, recent enforcement actions against component auditors, and the significance of these audits to the global economy. Yet research in this area is nascent. In response, we survey and interview US‐based global group audit leads to better understand the group audit process and their perceptions of challenges that arise on such engagements. Our findings indicate that group auditors organize their audits consistent with the client's structure, which drives component auditor selection, scoping, and fees. Group auditors routinely find fault with component auditors, perceiving that work performed and/or documentation provided is not sufficient, not appropriate and/or not communicated timely, to comply with US standards and reporting deadlines. In some cases, they perceive that the component auditor is unable and/or unwilling to comply and in others, that the component auditor misunderstands group instructions due to language proficiency or differing interpretation of the standards. Notably this perspective is ethnocentric, as group auditors almost exclusively attribute issues to component auditors. While ethnocentric tendencies appear myopic, they provide insight into unrecognized or overlooked aspects of the global firm model of cooperative arrangements. This study highlights the significance of the global firm's network structure to global group audits. Thus, we encourage intercommunity research, among (quantitative and qualitative) scholars and standard setters, to consider group audits in the broader context of firm networks.